Culture-Expanded Human Invariant Natural Killer T Cells Suppress T-Cell Alloreactivity and Eradicate Leukemia - Schmid, Hannes; Schneidawind, Corina; Jahnke, Simona; Kettemann, Felix; Secker, Kathy-Ann; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Kanz, Lothar; Savage, Paul B.; Schneidawind, Dominik (Frontiers in Immunology, 2018)
Graft-versus-host disease (GVHD) is a major cause of significant morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). Invariant natural killer T (iNKT) cells are potent regulators of immune responses, protect from lethal GVHD and promote graft-versus-leukemia (GVL) effects in murine studies. Since iNKT cells constitute less than 0.5% of human peripheral blood mononuclear cells (PBMCs), in vitro expansion with their glycolipid ligands is required before they can be used for cytotherapy and experimental pur-poses. Three weeks of cell culture and autologous restimulation with either KRN7000, PBS44 or PBS57 resulted in a robust proliferation of iNKT cells from human PBMCs. Next, iNKT cells were sorted to a purity higher than 90% being crucial for further experimental and clinical applications. These iNKT cells significantly decreased activation and prolifera-tion of allogeneic CD3+ T lymphocytes. In addition, leukemia cell lines and primary leuke-mia cells were efficiently lysed by culture-expanded iNKT cells. Importantly, culture-expanded donor iNKT cells promoted robust anti-leukemia activity against HLA-matched allogeneic patient leukemia cells. Our data indicate that the adoptive transfer of culture-expanded iNKT cells could be a powerful cytotherapeutic approach to induce immune toler-ance and prevent leukemia relapse after allogeneic HCT in humans.